A Comparative Study on Free Trade Zone: Development Through Spatial Economic Concentration - Adiwan F Aritenang (The Institute for Research and Community Services, Institut Teknologi Bandung, 2009)
Karena negara-negara mengalami keterbatasan sumberdaya, para peneliti dan pemerintah mencari alternative skema dan pola pembangunan. Dalam bidang Ilmu Regional, yang dimulai lima decade yang lalu, konsep kutub pertumbuhan yang muncul telah memperkenalkan fenomena multiplier effects dan trickling down. Ide ini telah diterjemahkan ke dalam berbagai konsep pembangunan, termasuk Kawasan Perdagangan Bebas (KPB). Tulisan ini bertujuan untuk memahami factor-faktor penentu yang berkontribusi secara signifikan pada performa ekonomi dan spillover extend KPB. Menggunakan analisa statistic, tulisan ini mempelajari perbandingan antara faktor-faktor kompetitif dan performa ekonomi dari tiga KPB di wilayah Asia, yaitu Batam (Indonesia), Subic (Filipina), dan Shenzhen (China). Dalam menentukan faktor-faktor kompetitif, tulisan ini mengikuti konsep Neo-klasik seperti local endowment, modal infrastruktur dan manusia, dan juga pendekatan kelembagaan dengan variabel-variabel termasuk kebijakan pemerintah and akses pasar. Penelitian ini mendapati bahwa performa ekonomi KPB bergantung pada kekonsistenan kebijakan pemerintah nasional dan local dan ketersediaan infrastruktur.Kata kunci: Kawasan Perdagangan Bebas, Geografi Ekonomi, Statistik perdagangan Batam As countries are limited on resources, governments and researchers seeks alternative schemes and forms of development. In the regional science subject, started in more than five decades ago concepts of growth pole emergence that introduce multiplier effects and trickling down phenomenon. This idea has been translated to various forms of development concepts, including the free trade zones (FTZ).This paper aims to understand the determining factors that contribute significantly to FTZ economic performance and spillovers extend. Using statistical analysis, this article studies the comparison of competitive factors and economic performances on three FTZ in the Asia region, which are Batam (Indonesia), Subic (Philippines), and Shenzhen (China). In determining competitive factors, this paper follows the idea of Neo-classical such as local endowments, infrastructure and human capital, and also institutional approach with variables including government policies and market access. The research found that economic performance of FTZ depends on local and national government policies consistency and infrastructure availability.Keywords: Free trade zone, Economic Geography, Batam Trade Statistics